2016
DOI: 10.1021/acs.energyfuels.6b01698
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Setups for Studying the Compatibility of Crude Oil Blends under Dynamic Conditions

Abstract: Blending of different crude oils is currently carried out in the petroleum industry. However, under certain process conditions, i.e., pressure, temperature, flow regime, composition, etc., asphaltene precipitation and plugging of pipelines and process equipment commonly occur, which cause production shutdowns; therefore, special cleaning programs need to be developed. To avoid these problems, it is first necessary to evaluate the compatibility of crude oil blends through a study of asphaltene stability. Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The colloidal instability index (CII), introduced by Asomaning and Watkinson to evaluate the propensity of residual oil to form sediments, is calculated based on the information about the oil SARA fractions in the oil . Other methods have also been postulated to predict the risk of asphaltene deposition that includes asphaltene instability trend (ASIST), colloidal stability index (CSI), stability index, Sepúlveda stability criterion (SCP), oil compatibility model (OCM), among others. Although these methods are the most widely used to distinguish very stable oils from very unstable ones, experience over the past years has shown that predictions tend to be somewhat pessimistic, indicating asphaltene precipitation in cases where no problems develop in the field.…”
Section: Introductionmentioning
confidence: 99%
“…The colloidal instability index (CII), introduced by Asomaning and Watkinson to evaluate the propensity of residual oil to form sediments, is calculated based on the information about the oil SARA fractions in the oil . Other methods have also been postulated to predict the risk of asphaltene deposition that includes asphaltene instability trend (ASIST), colloidal stability index (CSI), stability index, Sepúlveda stability criterion (SCP), oil compatibility model (OCM), among others. Although these methods are the most widely used to distinguish very stable oils from very unstable ones, experience over the past years has shown that predictions tend to be somewhat pessimistic, indicating asphaltene precipitation in cases where no problems develop in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Based on practical experience, there is a clear link between compatibility as measured using titration techniques and fouling in heat exchangers. Blending effects on fouling have been investigated for crude oils regarding their compatibility . In particular, it seems that the initial fouling rate could be correlated with the CII and that the addition of a crude oil with high solvent power can significantly decrease fouling even if added in small amounts .…”
Section: Introductionmentioning
confidence: 99%
“…12−15 Blending effects on fouling have been investigated for crude oils regarding their compatibility. 16 In particular, it seems that the initial fouling rate could be correlated with the CII and that the addition of a crude oil with high solvent power can significantly decrease fouling even if added in small amounts. 17 Besides compatibility, other characteristics of the crude oils are also linked to fouling and can be acting synergistically with asphaltene insolubility to accelerate fouling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to the complexity of the peptization, flocculation, and precipitation of asphaltene phenomena, several attempts of alternatives or modified methodologies for the measurement of crude oil stability have been reported. …”
Section: Resultsmentioning
confidence: 99%